ANALISIS BERTH OCCUPANCY RATIO DAN KAPASITAS TERMINAL PETI KEMAS PELABUHAN GORONTALO - Muchsin, Ria Septiani R; Kadir, Yuliyanti; Desei, Frice L. (Composite Journal, 2023)
There is an increase in the volume of containers, so there must be an evaluation of the capacity of the container terminal, so that there is no density of ship and container flows which can have an impact on the decline in the economy of the Gorontalo region. The purpose of this study is to analyze the capacity of the Gorontalo Port container terminal in 2021-2035. The research location is in the Port of Gorontalo which is located on Jalan Mayor Dullah, Talumolo Village, Gorontalo City. The method used is simple regression to find the value of the Berth Occupancy Ratio (BOR), the value of Berth throughput (BTP), the value of the dock capacity and the area of ​​the container field for the next 15 years. The results showed that the value of the Berth Occupancy Ratio (BOR) at the Port of Gorontalo in 2021 to 2035 the value of the Berth Occupancy Ratio (BOR) was above 40% of the value suggested by UNCTAD (United Nation Conference On Trade and Development). in the next 15 years the value of the Berth Occupancy Ratio (BOR) will reach 101.78%. For employment for the next 15 years from 2021 to 2035, it requires a field area of ​​5,094 m2–6,032 m2 and the current existing field at Gorontalo port is found to be 18,126 m2, which means the field at Gorontalo Port can still accommodate containers until 2035.